Some issues of small business development in Kazakhstan (Journal of Economic Research & Business Administration, 2016)
Development of small and medium business – the basis of any economy. Without the development of small and medium enterprises is difficult to talk about the stability of the macroeconomic situation, the state – cal. Consequently, at the dawn of independence of small and medium business in Kazakhstan it has been identified as an important sector of the economy. Comprehensive support for small and medium businesses has always been a priority of state policy.The problem of small business is always in the spotlight of the state. Through the development of the SME state solves a number of economic, political and social problems. It is generally accepted that small businesses are more competitive, they respond to the demand more quickly, require a minimum investment and use human resources more efficiently. However, the possibilities of SMEs are not fully implemented in the country. There are a number of factors constraining their development. The article discusses some of the issues of small businesses, the solution of which, according to the authors, contribute to the further development of SMEs in the country.
Keywords: small business; simplified taxation system; private enterprise; government support for small business.